A novel signature constructed by super-enhancer-related genes for the prediction of prognosis in hepatocellular carcinoma and associated with immune infiltration - Wei, Xueyan; Zhou, Zihan; Long, Meiying; Lin, Qiuling; Qiu, Moqin; Chen, Peiqin; Huang, Qiongguang; Qiu, Jialin; Jiang, Yanji; Wen, Qiuping; Liu, Yingchun; Li, Runwei; et al. (Frontiers in Oncology, 2023)
Super-enhancer (SE) refers to a regulatory element with super transcriptional activity, which can enrich transcription factors and drive gene expression. SE-related genes play an important role in the pathogenesis of malignant tumors, including hepatocellular carcinoma (HCC). The SE-related genes were obtained from the human super-enhancer database (SEdb). Data from the transcriptome analysis and related clinical information from the HCC were obtained from The Cancer Genome Atlas (TCGA) and the International Cancer Genome Consortium (ICGC) database. The upregulated SE-related genes from TCGA-LIHC were identified by the DESeq2R package. Multivariate Cox regression analysis was used to construct a 5-gene prognostic signature. According to the median risk score, HCC patients were divided into high-risk and low-risk group patients. The Kaplan-Meier (KM) curve showed that the prognosis of the high-risk group was significantly worse(P<0.001). In the TCGA-LIHC dataset, the area under the curve (AUC) values for predicting the 1-, 3-, and 5-years overall survival (OS) were 0.727, 0.767, and 0.690, respectively, indicating the good prediction ability of our prediction model. This model's prognostic value was further validated in the LIRI-JP dataset and HCC samples (n=65). Furthermore, we found that infiltration of M0 macrophages was higher in the high-risk group patients. In addition, higher levels of immune checkpoint molecules were found in the high-risk group, emphasizing that immunotherapy may be more effective in this patient population. These findings suggest that the novel SE-related gene model can be used to predict the prognosis of HCC patients.